Euro-Par 2007 Workshops: Parallel Processing - Bougé, L. (Springer, 2017)
Parallelanddistributedprocessing,althoughwithinthefocusofcomputerscience researchforalongtime,isgainingmoreandmoreimportanceinawidespectrum of applications. These proceedings aim to demonstrate the use of parallel and distributed processing concepts in di?erent application ?elds, and attempt to spark interest in novel research directions to advance the embracing model of high-performance computing research in general. The objective of these workshops is to speci?cally address researchers c- ing from university, industry and governmental research organizations and application-oriented companies, in order to close the gap between purely s- enti?c research and the applicability of the research ideas to real-life problems. Euro-Par is an annual series of international conferences dedicated to the promotionandadvancementofallaspectsofparallelanddistributedcomputing. The 2007 event was the 13th issue of the conference. Euro-Par has for a long time been eager to attract colocated events sharing the same goal of promoting the development of parallel and distributed computing, both as an industrial technique and an academic discipline, extending the frontier of both the state of the art and the state of the practice. Since 2006, Euro-Par o?ers researchersthe chance to colocate advanced technical workshops back-to-back with the main conference. This is for a mutual bene?t: the workshops can take advantage of all technical and social facilities which are set up for the conference, so that the organizational tasks are kept to a minimal level; the conference can rely on workshopstoexperimentwithspeci?careasofresearchwhicharenotyetmature enough, or too speci?c, to lead to an o?cial, full-?edged topic at the conference.